2021
DOI: 10.3390/sym13112145
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Symmetries in the Study of Vibration Response of a Hollow Cylinder

Abstract: The paper studies the vibration response of an elastic solid that has geometric symmetries. These determine special properties of the equations of motion of such a system, presented in the case of a cylindrical body (hollow cylinder). The properties of the eigenvalues and eigenmodes of these systems are theoretically established. A validation of these results is made using the finite element method. The use of the obtained results can lead to an easing of the vibration analysis of such a system and, consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The calculation time is related directly to the unknown quantity that existed in th finite element analysis (Mammoli 1999) [37]. The time taken to solve the equations wit the usual solution is proportional to the cube of the number of unknowns (Itu 2021) [38] The superelement method can also reduce the number of unknown quantities an speed up the analysis process (Qiu 2009) [39]. However, the loads for these types of struc tures are applied mainly to the top chord nodes, which must be set as the primary node Therefore, the number of unknown quantities reduced by the superelement method is no obvious.…”
Section: Mirroring and Basic Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation time is related directly to the unknown quantity that existed in th finite element analysis (Mammoli 1999) [37]. The time taken to solve the equations wit the usual solution is proportional to the cube of the number of unknowns (Itu 2021) [38] The superelement method can also reduce the number of unknown quantities an speed up the analysis process (Qiu 2009) [39]. However, the loads for these types of struc tures are applied mainly to the top chord nodes, which must be set as the primary node Therefore, the number of unknown quantities reduced by the superelement method is no obvious.…”
Section: Mirroring and Basic Blockmentioning
confidence: 99%
“…The calculation time is related directly to the unknown quantity that existed in the finite element analysis (Mammoli 1999) [37]. The time taken to solve the equations with the usual solution is proportional to the cube of the number of unknowns (Itu 2021) [38].…”
Section: Mirroring and Basic Blockmentioning
confidence: 99%
“…The statistics for this Special Issue related to published or rejected items were as follows [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]: 25 total submissions, 15 published papers (60%), and 10 rejected papers (40%). The geographical distribution of the authors of published papers is shown in Table 1, in which it can be seen that 50 authors are from seven different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%